FORMULATION OF HERBAL HARD CANDY CONTAINS RED GINGER (Zingiber officinale var. rubrum) EXTRACT - Nur Illiyyin Akib; Wa Baane; Adryan Fristiohady (Universitas Islam Negeri Alauddin Makassar, 2016)
Red ginger rhizome (Zingiber officinale var. Rubrum) contains alkaloid, flavonoid, saponin, tanin, and triterpenoid that potentially as antibacterial and also gingerol, shogaol, and zingeron are efficacious as antioxidant. Red ginger used as a flavour of hard candy because the essential oils gives characteristic and ginger scent, and also the oleoresin gives spicy ginger flavor. This research aims to find the best formula of hard candy through the hedonic test includes organoleptic, water content, ash content, and hardness. This research used four formulas that are K (without red ginger extract), A (extract of 1%), B (extract of 1.75%), and C (extract of 2.5%). Hedonic test data analyzed by Kruskal-Wallis test shows the addition of red ginger extract make significant effect on organoleptic properties (color, scent, texture, and flavor). The results of water content test of K, A, B, and C formulas respectively are 0.0023; 0.0086; 0.0054; and 0.0045%. The results of ash content test are 0.0031; 0.0039; 0.0049; and 0.0072%. The results of hardness test are 16.8; 6.8; 10.1; and 19.3 Kgf. The best formula is A that organoleptic characteristic (color, scent, flavor, and texture) are most preferred by panelists then result the tests of characteristics are accordance with quality requirements